ISOLATION OF DIESEL OIL DEGRADATION BACTERIA IN THE WATERS AROUND THE PORT OF TELUK BAYUR PADANG CITY - Sri Melinda Citra; Dessy Yoswaty; Nursyirwani Nursyirwani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Diesel oil degradation bacteria can be found in various habitats in the marine environment including in the waters around the harbor. This research aims at diesel oil in the waters around the port of Teluk Bayur and test its ability to degrade diesel oil. Isolation of the degrading bacteria has been from April to conductedJune 2018 in the Marine Microbiology Laboratory, Department of Marine Science, Faculty of Fishery and Marine University of Riau.Total count of diesel oil decomposing bacteria ranges from 0.4 x 106 to 7.3 x 106 CFU/ml. Eleven isolates of the diesel oil degradation bacteria were selected, ie BM1a, BM1b, BM1c, BM1d, BM7a, BM7b, BM7c, BM7d, BM14a, BM14c and BM14d. Based on morphological, physiology and biochemical characteristics, seven isolates were irregular, two round and concentric isolates, seven isolates with corrugated colony edges, two irregular and notched isolates, six yellow colony isolates, five white isolates, colony elevation all isolates emerge, all isolates were positive on catalase test, in H2S test all negative isolates, all isolates in the sugar test produced gas, all isolates were motile and Gram negative, all indole isolates were negative, seven methyl red positive isolates and four methy red isolates negative. In the degradation test only six bacterial isolates were selected, ie BM1a, BM1c, BM7a, BM7d, BM14c and BM14d. The highest degradation of diesel oil at concentrations 1%, 2% and 3% were performed by isolates BM1c, BM7a and BM1a respectively. Overall, all isolates were able to degrade diesel oil in the waters around Teluk Bayur Port, Padang City. Keyword: Isolation, Bacteria, Degradation, Diesel Oil